The Influence of Maternal Role Modeling and Emotional Style on the Politeness Character of Preschool Children in Sunda Indigenous Village - Mardhiyah Khoirunnisa; Dwi Hastuti (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2026)
Politeness character are a very important character trait that needs to be optimized from early childhood because they serve as a foundation for children to develop good social skills. The development of politeness character in children is influenced by the family environment, particularly the mother’s role in child rearing. This study aims to analyze the influence of a maternal role modeling and emotional style, which includes emotional coaching and emotional dismissing on the politeness character of preschool aged children in Sunda indigenous villages. This is a quantitative cross-sectional study using non-probability sampling methods, specifically purposive sampling and convenience sampling. Data were collected through in person interviews and questionnaires administered to 100 mothers and preschool aged children, with 26 respondents from Pasir Indigenous Village in Garut and 74 respondents from Naga Indigenous Village in Tasikmalaya. The results of this study indicate that the majority of mothers are at a moderate level in terms of role modeling, emotional coaching, and emotional dismissing. Similarly, the majority of children exhibit a moderate level of politeness character. Based on correlation tests, there is a relationship between family characteristics and children’s politeness character. Maternal role modeling is associated with the maternal emotional style. Furthermore, the maternal emotional style is associated with children’s politeness character. Family and child characteristics effect children’s politeness character. Meanwhile, maternal role modeling and emotional style were not found to effect children’s politeness character. Based on these findings, mothers are advised to adopt a more responsive and communicative parenting style, participate in various educational programs, and set aside dedicated time with their children on a regular basis